Key Case Law Rules for Government Contract Formation - Butler, Patrick (Berrett-Koehler Publishers, 2014)
Go Beyond the FAR! The guidance contained in the almost 2000 pages of the Federal Acquisition Regulation and the various agency supplements are just a part of the resources government acquisition professionals need to do their jobs effectively. Accessing and understanding case law is equally important to a thorough understanding of government contracting. Legal decisions explain the Government Accountability Office's and the courts' views on how procurement statutes and regulations apply in a wide range of situations. Case law also gives potential bid protesters and agencies a way to gauge the likely outcome of a protest. Until now, it has been difficult to find and understand the legal decisions that could be relevant to a particular situation. Key Case Law Rules for Government Contract Formationchanges that by organizing and explaining the most important protest grounds in a readily accessible and comprehensible way. With an emphasis on more recent cases, the book is organized around the key protest grounds, such as pricing issues, allegations that the government wrongfully prevented competition, or improper sealed-bidding procedures. Bridging the gap of understanding between the legal and the contracting communities, this book is a much-needed addition to the essential resources for acquisition professionals.